2019
DOI: 10.1590/s0102-053620190309
|View full text |Cite
|
Sign up to set email alerts
|

Soil water stress ranges: water use efficiency and Chinese cabbage production in protected cultivation

Abstract: Water deficit or water excess can affect development and yield of vegetables. The objective of this study was to evaluate the effect of different soil water stress ranges for Chinese cabbage (Brassica pekinensis) in a protected cultivation. The researches were carried out at the Olericulture Sector of Universidade Federal Tecnologica do Paraná between April and July, 2015 and January and April, 2016. Two Chinese cabbage cultivars were analyzed (Eikoo and Kinjitsu) with four soil water stress range (13-17, 23-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Brassica Chinensis is sensitive to nitrogen (N) and water stress because it is a leafy plant with a succulent stem (Kamarudin et al, 2014). It requires constant irrigation to achieve optimum production because leaf production is linked to leaf expansion, the most sensitive physiological process to water stress (Paulus et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Brassica Chinensis is sensitive to nitrogen (N) and water stress because it is a leafy plant with a succulent stem (Kamarudin et al, 2014). It requires constant irrigation to achieve optimum production because leaf production is linked to leaf expansion, the most sensitive physiological process to water stress (Paulus et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is in confirmation of the findings of [21], who observed that the highest water use efficiency in terms of marketability was achieved when irrigation led to a 30% depletion of the available soil moisture. [22] have obtained a higher water use efficiency for Chinese cabbage (42.1-47.3 kg m3) in the stress range of 13-17 kappa. As can be observed in Fig.…”
Section: Field Water Use Efficiencymentioning
confidence: 95%
“…ipsilon et a induit directement de faible performance, soit 22,9 t/ha. Les résultats de cette étude sont similaires à ceux obtenus au Brésil, où T. vogelii et Zingiber officinale avaient respectivement enregistré 57,2 t/ha et 30,2 t/ha en culture de chou de Chine avec le cultivar Eikoo (Paulus et al, 2019).…”
Section: Effet De Biopesticides Sur Le Rendement De Chou De Chineunclassified